Laser micro-structured Si scaffold-implantable vaccines against Salmonella Typhimurium. Issue 16 (10th April 2019) - Zerva, Ioanna; Katsoni, Eleni; Simitzi, Chara; Stratakis, Emmanuel; Athanassakis, Irene
Abstract: Salmonella Typhi is responsible for typhoid fever in humans. Despite the efforts, the development of long-lasting vaccines has failed and the available vaccines display only moderate activity, being considered as "international traveler's" vaccines. Taking advantage of the previously described implantable vaccine technology consisting on 3D laser-microstructured Si scaffolds loaded with antigen-seeded macrophages, the present study aimed to apply an antigenic stimulus of whole extracts of S. Typhimurium, which is the mouse analogue of the human Salmonella Typhi, and examine its ability to mount specific antibody response. After defining the experimental conditions for specific anti- S. Typhimurium IgG production in vitro, antigen-seeded macrophages loaded onto the 3D Si-scaffolds were implanted to mice, while parallel experiments used conventional Freund-complete-adjuvant vaccination protocols. The results showed that only the implantable vaccine protocol could mount a specific antibody response 14 days after implantation. The cytokine profile showed increase of IL-10 and IFN-γ in the case of implantable and conventional vaccination respectively, 7 days after implantation. Morphological studies on the excised scaffolds 14 days after implantation, showed the development of a well-structured adherent monolayer, establishing multiple contacts with lymphocytes in favor to immune response development. Based on the hypothesis that both stimulatory and suppressive components in the vaccination preparation, could affect the overall activity, peptidoglycan was applied as an antigen to the vaccination protocols. Surprisingly, peptidoglycan was shown to induce a mitogenic rather than specific immunogenic response. In this case, histological analysis of the excised scaffolds showed a restricted layer of adherent cells with cytoplasmic extensions, but hard to distinguish cell contacts with lymphocytes. Finally, the presented results showed a differential behavior of antigen presenting cells in accordance to the antigenic stimulus and consequently the activation state of the cells. Tailoring the micro/sub-micron 3D structures and chemistry of Si scaffolds, could control cell behavior according to the user's needs.